Effect of varying rates of commercially produced organic fertilizer on the growth and fibre yield of kenaf (Hibiscus cannabinus L.). (2016)
Hibiscus cannabinus L. or kenaf is a fast growing and multipurpose annual crop planted for its horticultural and economie importance. Little is known about its response to different rates of organic fertilizer in Nigeria. The objective of thè study was therefore to evaluate thè effeets of different rates of commercially produced organic fertilizer (Aleshinloye organic fertilizer to be precise) on crop growth rate, vegetative growth and biomass accumulation in kenaf Five different rates of organic fertilizer equivalent to: 0, 70, 100, 130 and 160 kg N ha'1 replicated three times were used in a randomized complete block design (RCBD). There were contrasting results on thè effects of fertilizer rates on growth and physiology of kenaf. Significant effects were observed for some agronomie parameters such as plant height, stem diameter and fibre yield. The application of organic fertilizer at varying rates increased thè bast fibre yield of thè Ifeken 400 variety of kenaf troni 67.29 g/m2 (control) to 98.70, 147.88 and 157.40 g/ni2, in those grown on soil amended with 70, 100 and 130 kg N ha'1 of organic fertilizer respectively. Organic fertilizer could be utilized for thè cultivation of kenaf in Nigeria but thè rate to apply depends on thè nutrient content of thè organic fertilizer.